The Open Sore of Football: Aggressive Violent Behavior and Hooliganism - Gumusgul Osman; Acet Mehmet (Sciendo, 2016)
Aggression and violence have been a customary part of life that mankind has had to live with from the beginning of time; it has been accepted by society even though it expresses endless negativity. Aggression and violence can find a place in sports events and football games because of the social problems of the audience watching the competitions or games, which sometimes fall into the category of hooliganism. Turkey is one of the countries that should consider this problem to be a serious social problem. Even during 2014 and 2015, a relatively short period of time, there were significant hazardous acts committed by hooligans. In February 2014, one supporter was killed after a game between Liverpool and Arsenal in England; in March 2014, a game between Trabzonspor and Fenerbahce was left half-finished because of violent acts in the stadium that caused players in the pitch to believe that they could not leave stadium alive, although they finally left after a few hours; in another incident in March 2014, one supporter was killed after a game between Helsingborg and Djugarden in Sweden; in November 2014, one supporter was killed and 14 supporters were injured before the game between Atletico Madrid and Deportivo in Spain. These are all examples of aggression, violence, and hooliganism in football. This paper aims to discuss aggression, violence, and hooliganism in football, especially in recent years, and investigate what can be done to prevent these acts from occurring again in the future by examining them in hindsight.